1994
DOI: 10.3109/00016349409013391
|View full text |Cite
|
Sign up to set email alerts
|

Is fetal heart rate variability a good predictor of fetal outcome?

Abstract: FHR variability by itself cannot serve as the only indicator of fetal wellbeing. The presence of low variability should alert the physician; however, good FHR variability should not be interpreted as reassuring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…In 1968 pregnancies the presence of moderate variability had 499% negative predictive value for adverse outcome, defined as 5-minute Apgar score 57, and 485% negative predictive value for umbilical arterial blood pH 57.2 [12]. In a further publication from the same group, it was concluded that in 2200 consecutive deliveries, fetuses with a normal FHR trace, or mild variable decelerations, or decreased FHR variability, or mild bradycardia, or accelerations present, in the last 30-minute segment recorded before delivery, had an Apgar score 7 in 99.7%, and umbilical arterial cord pH 7.15 in 96.9% of cases [13].…”
Section: Resultsmentioning
confidence: 98%
“…In 1968 pregnancies the presence of moderate variability had 499% negative predictive value for adverse outcome, defined as 5-minute Apgar score 57, and 485% negative predictive value for umbilical arterial blood pH 57.2 [12]. In a further publication from the same group, it was concluded that in 2200 consecutive deliveries, fetuses with a normal FHR trace, or mild variable decelerations, or decreased FHR variability, or mild bradycardia, or accelerations present, in the last 30-minute segment recorded before delivery, had an Apgar score 7 in 99.7%, and umbilical arterial cord pH 7.15 in 96.9% of cases [13].…”
Section: Resultsmentioning
confidence: 98%
“…A reduction in fetal heart rate variability (FHRV), particularly when it is combined with other fetal heart rate (FHR) abnormalities, is reported to be an important indicator of fetal hypoxia and developing acidemia both in the term (58) and preterm fetus (29). Perhaps surprisingly, however, many clinical studies have suggested there is either a weak or no relationship between FHRV and Apgar scores or cord acid-base measures during labor (37, 43). Indeed, the initial response to acute experimental hypoxemia or repeated asphyxia in the term fetus is an increase in FHRV rather than a decrease (9,24,33,55); typically FHRV then becomes suppressed if the insult is continued or repeated (16,20,33,55).…”
mentioning
confidence: 98%
“…Since the fetus is mainly inaccessible to direct measurement during pregnancy, most studies are either based on fetal heart rate patterns obtained by cardiotocography [2] or experiments on chronically instrumented animals [3]. Compared to the former, alternative, more precise tools such as magnetocardiogram or abdominal electrocardiogram offer significant improvements for the beat-to-beat analysis of FHR variability.…”
Section: Introductionmentioning
confidence: 99%